The fallacy of cosmopolitanism. A review of S. Benhabib’s theory - Crespo Catalán, Carmen (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
Transnational migrations, the integration of cultural pluralism in the host States of immigrants, the recognition of their civil, economic and political rights and the conditions of access to citizenship are issues of public interest that force us to rethink and renew the borders of democracy. The presence of irregular foreigners and the massive arrival of refugees at the gates of Europe have beaten the borders of our citizenship, calling into question EU community values and challenging the cosmopolitan tradition from outside the EU Administration. These practical contradictions force theorists of justice and political philosophy, such as S. Benhabib, to explore the limits of belonging, responsibility, and ethics in contemporary democracies. The objective of reconciling the rights of self-government and free territorial self-determination with the affirmation of universal human rights necessarily involves arguing the validity of the modern nation-state and problematizing the divisive logics of territorial sovereignty, so rein-forced today.
Keywords: refugees; Benhabib; citizenship; hospitality; rights of others